Penerapan Wasiat dalam Pembagian Harta Warisan Berdasarkan Tinjauan Yuridis - Al-Faiz, Ahmad Amhar; Suqma, Ahmad Rauf; Darmawan, Rakha; Lena, Sahara Reva; Syamsiah, Syamsiah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to analyze in depth the application of wills in the distribution of inheritance, reviewed from a juridical perspective both in Islamic law and positive law in Indonesia. The main purpose of this study is to find out more comprehensively about the legal provisions that govern wills, how the implementation of wills in the practice of inheritance distribution, and its impact on the creation of justice in the distribution of inherited inheritance assets to their heirs. The method used in this study is a qualitative method with a normative-juridical approach. This approach is carried out through a literature study that includes a review of various legal sources, official documents, and relevant literature. Among the legal documents studied in this study are Law Number 1 of 1974 concerning Marriage, the Compilation of Islamic Law (KHI), as well as various books and scientific journals that discuss wills and inheritance law. In addition, supporting data was obtained through direct interviews with religious leaders, legal practitioners, and employees of the Office of Religious Affairs (KUA) who have direct experience in handling inheritance issues. The results of the study show that a will in Islamic law is allowed with the provision that a maximum of one-third of the total inheritance property of the heir. The will should not be given to the legal heirs if it could reduce their predetermined inheritance rights. However, in practice, the implementation of a will is often not accompanied by legally valid written evidence, thus causing disputes and conflicts among the heirs. This problem is exacerbated by the low public understanding of inheritance law, both sharia and legal formality. From this study, it can be concluded that the application of a will in accordance with the applicable legal provisions can be an effective means in preventing family conflicts and maintaining justice in the distribution of inheritance. For this reason, it is recommended that there be regular training and counseling on inheritance law for the community, assistance from the KUA, and encouragement to make a will formally and legally valid so that its implementation is more guaranteed.